(untitled) (Sirte Journal of Medical Sciences, 2025)
Background: Cervical cancer (CC) is a preventable and treatable gynaecological disease. Preventive medicine plays an essential role in the reduction of CC morbidity and mortality rates. Healthcare workers in developing countries have not demonstrated a comprehensive awareness and knowledge of CC prevention and early detection. Objective: The aim of this study is to examine the awareness about CC and its risk factors and describe the level of knowledge for role of Human Papilloma Virus (HPV) infection in CC and the use pap smear screening tests among female students and graduates at the Faculty of Public Health at the University of Benghazi, Libya. Participants and Methods: A cross-sectional, descriptive study was conducted during the period 14th and 25th of July 2024, targeting the female students and graduates of Public Health Faculty in Benghazi- Libya. Ethical approval was obtained from the ethical committee of the faculty. Sample size was calculated to be 360 participants. Consents of participation were obtained. The questionnaire was distributed to students (year one to year four and to the graduates) answers collected through Google form. We started analysis when the desired sample size reached nearly equal distributions between the four years students and the graduates. The questionnaire consisted of two parts: socio-demographic characteristics, (age, year of study, role at faculty (students or graduates), and marital status). The second part consisted of knowledge about CC causes, risk factors, awareness about HPV (sexually transmitted infection, types associated with CC and vaccination). Pap smear as screening test for early detection of cervical changes. Personal practice through asking about receiving HPV vaccination, enumerating the common barriers to implement CC prevention programs, SPSS version 27 was used